124k views
1 vote
Y=4x + 6
Y = 6x - 12

Solve the systems of equation by substitution

User TheZuck
by
4.6k points

1 Answer

6 votes

Answer:

x=9, y=42

Explanation:

y=4x+6

y=6x-12

Substitute the second equation into the first:

6x-12=4x+6

Subtract 4x from both sides:

2x-12=6

Add 12 to both sides:

2x=18

Divide both sides by 2:

x=9

Plug this back into one of the equations to find y:

y=4(9)+6=36+6=42

Hope this helps!

User Prashant G Patil
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.